Genetic aetiology of early infant deaths in a neonatal intensive care unit. Issue 3 (9th September 2019) - Yang, Lin; Liu, Xu; Li, Zixiu; Zhang, Peng; Wu, Bingbing; Wang, Huijun; Hu, Liyuan; Cheng, Guoqiang; Wang, Laishuan; Zhou, Wenhao
Abstract : Background: Congenital anomalies are the leading cause of early neonatal death in neonatal intensive care units (NICUs), but the genetic causes are unclear. This study aims to investigate the genetic causes of infant deaths in a NICU in China. Methods: Newborns who died in the hospital or died within 1 week of discharge were enrolled from Children's Hospital of Fudan University between January 1, 2015 and December 31, 2017. Whole exome sequencing was performed in all patients after death. Results: There were 223 deceased newborns with a median age at death of 13 days. In total, 44 (19.7%) infants were identified with a genetic finding, including 40 with single nucleotide variants (SNVs), two with CNVs and two with both SNVs and CNVs. Thirteen (31%, 13/42) patients with SNVs had medically actionable disorders based on genetic diagnosis, which included 10 genes. Multiple congenital malformation was identified as the leading genetic cause of death in NICUs with 13 newborns identified with variants in genes related to multiple congenital malformations. For newborns who died on the first day, the most common genetic cause of death was major heart defects, while metabolic disorders and respiratory failure were more common for newborns who died in the first 2 weeks. Conclusion: Our study shows genetic findings among early infant deaths in NICUs and provides critical genetic information for precise genetic counselling for the families. Effective therapies enable the improvement of more than a quarter of newborns with molecular diagnoses if diagnosed in time.